Do Organizational Interests Interfere with Public Communication of Science? An Explorative Study of Public Relations of Scientific Organizations in Taiwan. Issue 4 (1st December 2019) - Lo, Yin-Yueh; Huang, Chun-Ju; Peters, Hans Peter
Abstract: The relevance of public relations (PR) efforts of scientific organizations for public communication of science is increasingly recognized. PR departments are not mere mediators between scientists and journalists but represent the stakeholder interests of their organizations in the public sphere and are communicative actors themselves. Previous Taiwanese studies focused on university PR in the educational context, whereas the potential function in the communication of research and scientific knowledge received less attention. This study explores how PR departments of academic organizations in Taiwan view their role in the public communication of science. Insights from eleven semistructured interviews with PR officers suggest that public relations departments of academic organizations in Taiwan only half-heartedly contribute to the communication of science. Another interesting finding is that even in the era of social media science, PR still relies heavily on journalism, which in Taiwan lacks professionalism in the communication of science. We suggest a more active role of academic organizations in the public communication of science, pursuing not only marketing or self-presentation goals, but also assuming genuine responsibility for public information about research and scientific knowledge.